Integrated Positioning for Coal Mining Machinery in Enclosed Underground Mine Based on SINS/WSN. (21st January 2014) - Fan, Qigao; Li, Wei; Hui, Jing; Wu, Lei; Yu, Zhenzhong; Yan, Wenxu; Zhou, Lijuan
Abstract : To realize dynamic positioning of the shearer, a new method based on SINS/WSN is studied in this paper. Firstly, the shearer movement model is built and running regularity of the shearer in coal mining face has been mastered. Secondly, as external calibration of SINS using GPS is infeasible in enclosed underground mine, WSN positioning strategy is proposed to eliminate accumulative error produced by SINS; then the corresponding coupling model is established. Finally, positioning performance is analyzed by simulation and experiment. Results show that attitude angle and position of the shearer can be real-timely tracked by integrated positioning strategy based on SINS/WSN, and positioning precision meet the demand of actual working condition.